Body Mass Index (BMI) is a Risk Factor for Coronary Artery Disease (CAD) - Daradkeh, Ghazi; Haider, Farrookh; Al Obahi, Asma; Al Muhannadi, Asma (British Journal of Healthcare and Medical Research, 2024)
Background: Although excess adiposity appears to increase the risk of coronary artery disease (CAD) in the general population, its importance in patients with established coronary disease is less defined. Aims: We evaluate a population-based inception cohort of survivors retrospectively as a review to assess the association between body mass index (BMI) and the risk of coronary artery diseases. Methods: literature search in PubMed was done by using the following keywords combination: (cardiovascular diseases or heart disease or coronary artery disease) and body mass index BMI. Screened the topics and removed duplicates, papers that contained abstracts only or papers that had no access to the full article were excluded from the study. This review article has retrieved 51 papers through a PubMed search. The first screening was to remove duplicates (n = 13), followed by removing articles with only an abstract or without access to the entire research (n = 16). Finally, a complete research revision revealed non-eligible papers (n = 29). A final number of (n = 22) research was included. Results: all 22 articles were full-text free downloads from PubMed. Conclusion: Obesity is a significant component of metabolic syndrome. A greater risk of CAD is associated with an increased BMI and metabolically unhealthy people. Metabolically unhealthy obese people have a greater risk of coronary artery disease when compared to metabolically healthy obese people. Additionally, it has been proven that obese people can benefit from losing weight and physical activity.